Protección de antioxidante de zarzamora para disminuir daño muscular en atletas de elite. - García Dávila, Myriam Zaraí; Rangel Colmenero, Blanca Rocío; González Martínez, Blanca Edelia; Gutiérrez Soto, Juanita Guadalupe (Universidad Autónoma de Barcelona, 2017)
Abstract High intensity physical activity can provoke muscle damage and consequently affect athletes’ performance. The aim of this study was to determine if antioxidants contained in blackberry can stimulate athletes’ processes of recovery from muscle damage, using Creatine Kinase (CK) quantification and urea values after a week of competition as indicators. Participants were divided into an experimental (EG) and a placebo group (CG). In both groups, CK and urea in plasma were measured before, during and after competition. Significant differences were observed in EG at pre and post phases, compared to the basal (p < 0.05). Further, significant differences were found in the pre-post analysis of EG (p < 0.05), as well as after 48h and 72h compared with post-test (p < 0.05). Significant differences were also found for CG (p < 0.05) at 48h and 72h compared to post-test. As regard to urea concentration, differences were shown at post-test, after 24h, and after 48h compared to pre-test (p < 0.05). CG showed no significant differences at any stage of the research. These results suggest that consumption of blackberries may contribute to muscle damage recovery.